2006
DOI: 10.1111/j.1365-2842.2006.01674.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status in war veterans with post‐traumatic stress disorder

Abstract: The aim of this study was to assess the oral health condition of Croatian war veterans with post-traumatic stress disorder (PTSD). The study included 50 men who experienced combat stress and had been diagnosed with PTSD. They were compared with the group of 50 age-matched men who did not participate in war and did not have PTSD. Xerostomia, oral mucosal lesion, oral hygiene status, dental, and periodontal conditions, as well as temporomandibular disorders (TMDs) were assessed and compared between the groups. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 22 publications
2
42
2
1
Order By: Relevance
“…Muhvić-Urek et al 8 Case-control 50 war veterans with PTSD 50 healthy subjects 100% men TMD prevalence was 48% in the veterans and 8% in the control group. The most common diagnosis was myofascial pain among veterans and disc displacement in the control group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Muhvić-Urek et al 8 Case-control 50 war veterans with PTSD 50 healthy subjects 100% men TMD prevalence was 48% in the veterans and 8% in the control group. The most common diagnosis was myofascial pain among veterans and disc displacement in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…After sorting the titles and abstracts, 12 articles were selected for a complete reading of the texts. From these, six meet the inclusion criteria [6][7][8][17][18][19] . One paper was excluded because it did not evaluate the relationship between TMD and PTSD 20 and five because they did not use diagnostic criteria validated for TMD, only evaluating signs and symptoms of dysfunction in the studied population [21][22][23][24][25] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Suman et al (2008) investigated the effect of the war on oral health among professional soldiers and found the number of decayed, filled and missing teeth was significantly higher (DMFT 14.4) among those who had been in combat than among those who had not (DMFT 13.1) [14]. Muhvic-Urek et al (2007) studied dental status of war veterans of the Croatian army suffering from post-traumatic stress disorder and found that they had higher DMFT values than the control group, although the difference was not statistically significant [23]. Vered and Sgan-Cohen (2003) carried out a questionnaire survey on 4920, 21-year-old young Israeli people on compulsory military service, asking them how they assessed the status of their own teeth.…”
Section: :Temperament and Character Inventorymentioning
confidence: 99%